Impaired driving due to alcohol or drugs: International differences and determinants based on E-Survey of Road Users' Attitudes first-wave results in 32 countries. (October 2020) - Goldenbeld, Charles; Torfs, Katrien; Vlakveld, Willem; Houwing, Sjoerd
Abstract: Introduction: Driving while intoxicated is a major risk factor for road traffic crashes, and it is important to understand the global developments, differences between countries, and determinants of driving while intoxicated. Because objective data are often missing, it is useful to investigate self-reported data. Method: The E -Survey of Road Users' Attitudes (ESRA2) on attitudes and behaviours in traffic—performed in 21 countries in Europe and 32 countries worldwide—was used to study the prevalence of self-reported impaired driving, national differences, changes over time, and factors that determine impaired driving and multiple traffic offences. Descriptive statistics and regression analyses were used. Results: In the European Union (EU), represented in the survey by 20 member states, 13% of car drivers reported to have driven under the influence of alcohol in the past 30 days, and 5% reported to have driven under the influence of drugs. For the participating countries in Africa, North America, and Asia/Oceania, these percentages were almost the same for drinking and driving (resp. 14%, 11%, 17%) but were clearly higher for drug driving (18%, 12%, 18%). Drivers who reported drinking and driving, drug driving, or multiple traffic offences also reported significantly higher involvement in injury crashes than other drivers. Regression analyses indicated that previous experience with drinking and driving was the strongest predictor for current drinking and driving; additionally, for drug driving, the perceived personal and social acceptance of this risky behaviour were the strongest predictors. Conclusions: Drinking and driving is a common risky behaviour worldwide, with an average of between 11% and 17% of drivers in major regions reporting to have engaged in this behaviour in the last month. Drug driving is less frequently reported in Europe than drinking and driving, but in Africa, North America, and Asia/Oceania, drug driving is reported as much or even more frequently. Highlights: Self-reported driving over the legal limit varies from 11% in the EU to 17% in Asia/Oceania. Drivers reporting multiple offences vary from 2% (EU) to 7% (Asia/Oceania). Six countries identified increased odds of self-reported drinking and driving and of drivers engaging in drugged driving. Multiple offenders have the greatest odds of being involved in (self-reported) injury crashes. Impaired driving and multiple offences are linked to various violation-related beliefs.